Pattern of Congenital Heart Diseases in Paediatric Age Group - Hafiz Muhammad Umer , Muhammad Usman Arshad, Furqan Mudassar, Abd Ul Slam , Saad Junaid, Rai Muhammad Asghar, Faiza Aslam (Journal of Rawalpindi Medical College, 2018)
Background: To determine the pattern of different types of congenital heart diseases, in paediatric age group. Methods: In this observational cross sectional study cases of congenital heart defects (CHD) were included, through simple random sampling irrespective of age and gender. Every patient’s data on echocardiographic report clearly indicating his CHD type along with age and gender was recorded. Variables of study i.e. type of CHDs, age, and gender with relative frequencies were presented separately graphically. Results: Out of 298 diagnosed patients of CHD 156 were males and 142 were females. Isolated ventricular septal defect found to be the most common anomaly (32.6%). In combination atrial septal defect and ventricular defect were found to be most common with 5.4% burden rate. Out of 298 patients Acyanotic CHDs were 67.1% while Cyanotic CHDs were found to be 32.9%. Conclusion: Acyanotic CHDs were found to be dominant over Cyanotic CHDs with relative percentages of 67.1% and 32.9% respectively